2018
DOI: 10.4103/jrms.jrms_72_18
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead levels in pregnant women referring to midwifery clinic in a referral center in Tehran

Abstract: Background:Lead effects on children and pregnant women are grave, and screening tests would be logical to detect high blood lead levels (BLLs) in early stages.Materials and Methods:Blood samples were taken from the pregnant mothers who referred to midwifery clinic with further phone interview postdelivery.Results:In 100 patients evaluated, the mean age was 29 ± 5 years (median interquartile range gestational age of 33 [24, 37] weeks). There was a significant correlation between polluted residential area and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Simultaneous presence of lead poisoning and anemia has also been mentioned in the previous studies. Lead interferes with the production of heme [18][19][20][21]. In fact, during the heme production, two pivotal enzymes (5-aminolevulinic acid dehydratase and ferrochelatase) are inhibited [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneous presence of lead poisoning and anemia has also been mentioned in the previous studies. Lead interferes with the production of heme [18][19][20][21]. In fact, during the heme production, two pivotal enzymes (5-aminolevulinic acid dehydratase and ferrochelatase) are inhibited [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Capillary blood lead levels were checked by Lead Care II device using voltametry method. This device determines the BLLs between 3.2 to 65 μg/dL [18]. The levels below and above these limits are determined as "low" and "high" levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Capillary blood lead levels were checked by Lead Care II device using voltametry method. This device determines the BLLs between 3.2 to 65 µg/dL [18]. The levels below and above these limits are determined as "low" and "high" levels.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the previously performed pilot study on 93 patients which showed an average frequency of BLLs higher than 10 µg/dL to be about 47.3% [18], the desired 95% level of confidence, and the desired ± 1.8 µg/dL accepted margin of error, a sample size of 142 was determined. Sixty-seven patients were expected to have BLLs higher than 10 µg/dL.…”
Section: Sample Sizementioning
confidence: 99%